Pola Penambahan Larutan Tawas untuk Penurunan Kekeruhan Air Sungai Martapura - Noraida Noraida (Politeknik Kesehatan Tanjung Karang, 2018)
Most of the Martapura River water in Tambak Anyar Village is used by the community for daily needs such as bathing and washing. Physically Martapura River water in Tambak Anyar Village does not meet the requirements seen in terms of turbidity to be used as a source of clean water. Water sources that do not meet the requirements must be processed before they are used. It is known that the turbidity of Martapura River water does not meet the standards of clean water according to the Minister of Health Regulation No. 416/MENKES/PER/IX/1990, the level of turbidity of the clean water is a maximum of 25 NTU. Turbidity in water can be caused by suspended and dissolved organic and inorganic substances such as mud, fine sand, plankton, and other microorganisms. This research is an experimental study. The aim of the study was to create a model for adding alum solution to Martapura river water with turbidity and pH parameters. The results of the study showed that the level of turbidity of water along the river Tambak Hanyar Martapura village ranged between 101-904 NTU and the water pH ranged between 6.31-6.60. The dosage of alum solution to decrease the turbidity level of river water in Tambak Hanyar Village up to 25 NTU ranged from 0.100 to 2.946 ml. Distance regression model with alum dosage and pH at 25 NTU turbidity is Alum Dose=0.122+0.455. (Distance). Doses in milliliters (ml) and distance in kilometers (km). It is suggested that the regression equation for decreasing the level of turbidity using the alum solution can be used according to the sampling point that has been done.